Toxicity of phosphate enemas - an updated review - Hamilton Smith, Rosa; Eddleston, Michael; Bateman, D. Nicholas (Clinical toxicology (Philadelphia, Pa.), 2022)
Enemas containing phosphate are widely prescribed and may cause important adverse effects. A systemic review published in 2007 reported the literature on the adverse effects of phosphate enemas from January 1957 to March 2007 and identified 12 deaths. These were thought due to electrolyte disturbances, heart failure and kidney injury. These data raised concerns about the use of phosphate enemas in routine practice. Newer osmotic-based enema alternatives are now available that do not contain absorbable ions. We sought to review the literature since this review and evaluate the latest data on the toxicity of phosphate-containing enemas. To gain a fuller picture we included case series and larger studies as well as case reports. To review the toxicity of phosphate enemas, particularly with respect to acute metabolic consequences and their associated clinical features. To identify risk factors for metabolic toxicity and consider whether phosphate enemas should be relatively contra-indicated in specific patient groups. A systematic literature review was conducted in PubMed, Google Scholar, and Cochrane Reviews (2005-2021) using the search terms 'phosphate enema or sodium phosphate enema' or 'phosphate-based enema' or (phosphate AND enema) or (Fleet AND enema) or 'sodium phosphate laxatives' or 'sodium phosphate catharsis' or 'sodium phosphate cathartic'. Relevant papers were read, and data were extracted. The searches identified 489 papers of which 25 were relevant: seven papers were case reports or small case series of metabolic abnormalities from the use of phosphate enemas in nine children, six were case reports on 16 adults. Nine papers were large case series or clinical studies that included data on systemic metabolic effects, of varying size from 24 healthy volunteers to a cohort of 70,499 patients. Case reports identified seven adult deaths but none in children. Children most often presented with decreased consciousness (6/9), and tetany (4/9). In adults overall only five cases had clinical features reported, hypotension was seen in four and QT prolongation in two. Treatment was generally symptomatic, with intravenous fluid and calcium salts for electrolyte changes and hypocalcaemia, and vasopressors for severe hypotension. Haemodialysis was used in three children and peritoneal dialysis in one, all of whom survived. In adults, haemodialysis did not prevent death in two of four cases in whom it was used. Common factors underlying toxicity were inappropriately high phosphate dose, or enema retention, both resulting in greater absorption of phosphate. Associated pre-disposing conditions included Hirschsprung disease in children and co-morbidity and renal impairment (2/5) in older adults. Absolute reported changes in serum phosphate or calcium were not accurate indicators of outcome. Larger case series and clinical trials confirm an acute effect of phosphate enemas on serum phosphate, which was related to both dose and retention time. These effects were not seen with non-phosphate preparations. In these cases series, adverse events were rarely reported. Phosphate enemas are potentially toxic, particularly in young children with Hirschsprung disease and in the elderly with co-morbidity. Raised awareness of the risk of phosphate enemas is still required. Other less toxic enema preparations are available and should be considered in patients at extremes of age. If phosphate enemas are the only clinical option careful monitoring of biochemical sequelae should be undertaken.